2009
DOI: 10.3844/ajeas.2009.202.211
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Performance Evaluation: Trends and Challenges

Abstract: Problem statement: In today's manufacturing world, globalization policies and rejuvenation have created a more intensive competition amongst manufacturers. On the other hand, manufacturers have turned to the option of adopting innovative technologies, process re-engineering and strategies such as efficient supply chain management to achieve a sustainable competitive advantage. Effective supply chain performance measurement has been identified as a key issue towards efficient supply chain management. To explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…But the firm must have devices for ensuring accurate measurement that employees have confidence in and which allow the firm to make fair judgments regarding their use and future needs of human resources. Therefore it is essential that human resource managers know when to use appropriate types of evaluation (Olugu and Wong, 2009). At times, MBO will be useful.…”
Section: Resultsmentioning
confidence: 99%
“…But the firm must have devices for ensuring accurate measurement that employees have confidence in and which allow the firm to make fair judgments regarding their use and future needs of human resources. Therefore it is essential that human resource managers know when to use appropriate types of evaluation (Olugu and Wong, 2009). At times, MBO will be useful.…”
Section: Resultsmentioning
confidence: 99%
“…But the firm must have devices for ensuring accurate measurement that employees have confidence in and which allow the firm to make fair judgments regarding their use and future needs of human resources. Therefore it is essential that human resource managers know when to use appropriate types of evaluation (Olugu and Wong, 2009). MBO is useful.…”
Section: Discussionmentioning
confidence: 99%
“…Chopra et al (2005;2007) evaluate the error that results from "bundling" disruptions and yield uncertainty when making inventory decisions. Related research also can be found in (Cachon and Fisher, 2000;Olugu and Wong, 2009;Lin and Chen, 2009).…”
Section: Introductionmentioning
confidence: 99%